Merawat Harmoni Agama melalui Kolaborasi Musik Hadroh dan Trompet di Ambon - Dewi Tika Lestari (UIN Sunan Gunung Djati Bandung, 2020)
This article aims to describe the role of music for preserving religious harmony after the social-religious conflict that occurred in 1999-2004 in Maluku. The study is conducted toward the collaboration of musicians of the music of hadroh which come from the Muslim community and the music of trumpet which come from the Christian community in Ambon City. This study uses a qualitative research approach with a discourse analysis approach. The study shows that both of the musical instruments, hadroh and trumpet, are always used in religious rituals, both in Islam and Christian. The musicians are also fromthese two religions. This study also found that Muslim and Christian can collaborate to provide a new style and introduce a new approach for maintaining peace in Maluku. As a result, this study shows that music has the power to preserve peace in a pluralistic society.